Classification criteria of antiphospholipid syndrome ACR/EULAR 2023 and comments on them - T. M. Reshetnyak (Научно-практическая ревматология)
Many rheumatic diseases are a model of human pathology disease. These are inflammatory rheumatic diseases, autoinflammatory and autoimmune diseases. Antiphospholipid syndrome (APS) is a model of antibody-induced thrombosis or acquired thrombophilia. In 2023, classification criteria were published, which were developed jointly by the American College of Rheumatology (ACR) and EULAR (European League against Rheumatism) and included a four-stage methodology. This review presents the existing APS classification criteria until 2023 and the 2023 criteria with their explanation.Conclusion. The classification criteria of ACR/EULAR 2023 reflect the multi-organicity and multidisciplinarity of this symptom complex. At the same time, like all classification criteria, they are designed to select homogeneous groups in clinical trials.